Problematika Implementasi Kurikulum Merdeka: Studi Kasus Pada SMP Negeri 2 Sipoholon - Sonia Widia Sipahutar (CV Putra Publisher, 2024)
This research aims to find out and explain the problems that occur in implementing the independent curriculum at SMP Negeri 2 Sipoholon. Departing from the many phenomena and policies related to the implementation of the independent curriculum, this gave rise to various questions for researchers such as the problems faced at SMP Negeri 2 Sipoholon in implementing the Independent Curriculum. This research was conducted using qualitative methods, namely field studies through field observations and interviews. The data at SMP Negeri 2 Sipoholon studied by researchers was collected through observations and interviews with the school principal, curriculum representatives and teacher council. Analyzed and presented in descriptive form. The results of this analysis can help answer research questions. The results of the analysis show that the Independent Curriculum at SMP Negeri 2 Sipoholon faces several problems, such as teachers having difficulty adapting to a more flexible curriculum and requiring more time to develop lesson materials that suit student needs. Teachers must be given further training to adapt a more flexible curriculum and improve their ability to develop learning materials that suit students' needs.